2007
DOI: 10.1002/hup.865
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with amisulpride and olanzapine improve neuropsychological function in schizophrenia

Abstract: Both amisulpride and olanzapine produce sustained improvement in certain measures of neuropsychological performance in patients with schizophrenia; a significant improvement in score on the AVLT was observed only with amisulpride.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Patients were found to perform markedly worse than control subjects for all six cognitive domains, and for all individual tests, except for a few concentration, visuo-spatial construction, and motor speed tasks. More pronounced cognitive dysfunctions found in patients compared to siblings and controls could be partially explained by side effects of psychotropic medications that can exert significant effects on cognitive functions (Keefe et al 2007;Mortimer et al 2007;Voruganti et al 2007). Siblings performed worse than the control group with P values indicating a trend towards statistical significance for a number of cognitive variables.…”
Section: Discussionmentioning
confidence: 86%
“…Patients were found to perform markedly worse than control subjects for all six cognitive domains, and for all individual tests, except for a few concentration, visuo-spatial construction, and motor speed tasks. More pronounced cognitive dysfunctions found in patients compared to siblings and controls could be partially explained by side effects of psychotropic medications that can exert significant effects on cognitive functions (Keefe et al 2007;Mortimer et al 2007;Voruganti et al 2007). Siblings performed worse than the control group with P values indicating a trend towards statistical significance for a number of cognitive variables.…”
Section: Discussionmentioning
confidence: 86%
“…This was partly replicated98 in a comparison of amisulpride and olanzapine: patients’ cognition improved on both drugs, thus detracting from the notion that 5HT2A antagonism was a necessary prerequisite for antipsychotic drug induced enhancement of cognition in schizophrenia. A more recent randomized 6-month trial of acute patients again demonstrated cognitive improvements on both olanzapine and amisulpride99 but there was a particular advantage for amisulpride in a verbal memory test.…”
Section: Amisulpride and Cognitionmentioning
confidence: 96%
“…Thus, despite having a pharmacological profile reminiscent of a typical antipsychotic in that it exhibits high D 2 affinity and low 5-HT 2A affinity, amisulpride therapeutically resembles atypical antipsychotics. Amisulpride has also been reported to improve the cognitive domains of attention, executive function, and working memory, as well as the global cognitive index in patients with schizophrenia (Deeks and Keating 2008), and declarative memory in another study (Mortimer et al 2007). However, it has also been shown to impair recognition memory in normal subjects (Gibbs et al 2008), (Mortimer et al 2007).…”
Section: Introductionmentioning
confidence: 95%